The Impact of Carbon Emission Disclosure and Green Innovation on Company Value: Moderating Role of Environmental Performance - Oriska, Selvia; Kusumawardani, Niken (InJEBA : International Journal of Economics, Business and Accounting, 2024)
This study investigates the impact of carbon emission disclosure and green innovation on corporate value, moderated by environmental performance, among Indonesian manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2022. Drawing on data from annual and sustainability reports, as well as PROPER evaluations, the research employs a purposive sampling method to select 55 relevant companies. Findings reveal that carbon emission disclosure significantly enhances corporate value, indicating the importance of transparency in addressing environmental concerns and attracting stakeholders. Similarly, green innovation positively influences corporate value, highlighting its role in bolstering environmental stewardship and stakeholder approval. However, environmental performance, measured through PROPER ratings, does not significantly moderate these relationships, suggesting that while high environmental performance ratings may enhance credibility, they do not necessarily drive extensive carbon disclosure or green innovation efforts. These findings underscore the need for companies to prioritize transparent carbon reporting and proactive green initiatives to enhance both financial performance and environmental sustainability. Future research directions could explore additional variables like eco-efficiency and corporate social responsibility to further enrich understanding of sustainable corporate practices and their impact on valuation.